Simulation of dust grain charging under tokamak plasma conditions. (August 2017) - Liu, Zhuang; Wang, Dezhen; Miloshevsky, Gennady
Highlights: The DS code is developed for dust charging processes simulation under tokamak conditions. The dust particles can be negatively or positively charged and the number of charges on the dust grain can reach the order of 10 to 10, 000. The charging time can be in the order of ns to ten µs and is inversely proportional to dust grain radius and plasma density. This work can be used as validation for future Particle-In-Cell simulation work. Abstract: Dust grains in fusion devices may be radioactive, contain toxic substances, and may penetrate into the core plasma resulting in the termination of plasma discharges. Therefore, it is important to study the charging mechanisms of dust grains under tokamak's plasma conditions. In this paper, the charging processes of carbon dust grains in fusion plasmas are investigated using the developed dust simulation (DS) code. The Orbital Motion Limited (OML) theory, which is a common tool when solving dust-charging problems, is used to study the charging of dust grains due to the collection of plasma ions and electrons. The secondary electron emission (SEE) and thermionic electron emission (TEE) are also considered in the developed model. The surface temperature of dust grains (Td ) is estimated for different plasma parameters. Floating potentials have been validated against the data available from the dust simulation code package DUSTT. It is shown that the dust grains are negatively charged for relatively low plasma temperatures below 10 eV and plasma densities below 10 19 m − 3 . For higher plasma temperature and density, however, the charge on dust grains may become positive. The charging time depends not only on the grain's size, but also on the plasma temperature.